2018
DOI: 10.1002/oa.2664
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in the historical population of Radom (Poland) from the 11th to 19th centuries

Abstract: Periodontitis can be an excellent indirect source of data on the general and oral health, dietary habits, and hygiene of past populations. This study assessed periodontitis in the population of Radom from the 11th century up to the industrial revolution in the 19th century. The dental material was divided into 3 historical series: the Early Medieval (EMP; 11th century), Late Medieval (LMP; 14th–17th century), and Modern (MP; 18th–19th century) periods. A total of 256 adult individuals of both sexes were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Many studies conducted so far indicate a higher prevalence of periodontitis in males (Kozłowski and Florkowski 1996, Garłowska 2001, Wasterlain et al 2011, Bonsall 2014, Novak 2015, Tomczyk et al 2018. Also in the studied population, both frequency and intensity were higher in this group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Many studies conducted so far indicate a higher prevalence of periodontitis in males (Kozłowski and Florkowski 1996, Garłowska 2001, Wasterlain et al 2011, Bonsall 2014, Novak 2015, Tomczyk et al 2018. Also in the studied population, both frequency and intensity were higher in this group.…”
Section: Discussionmentioning
confidence: 48%
“…In archaeological populations, the most important environmental factor was severe dental attrition. Dental wear beyond the contact points of neighboring crowns contributed to the formation of inter-2012, Tomczyk et al 2018). In general, the absence of uniform methods hinders the comparison of data reported by different authors.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that studies of historical populations are often on significantly damaged skeletal material, which could affect the gaps in our knowledge about the frequency of mesiodens in past populations. However, it should be emphasized that some bone collections in Poland (Tomaszewska & Kwiatkowska, 2019; Tomczyk et al, 2018), Norway (Evensen & Ogaard, 2007) and/or Croatia (Vodanović et al, 2012) have been radiologically tested and no mesiodens was found. Therefore, it would be of interest to determine in further studies whether any geographical variation was evident in past populations.…”
Section: Discussionmentioning
confidence: 99%
“…General (systemic) enamel hypoplasia affects at least two or more teeth, which is caused by the general disorder of the body's functioning. This disorder may result from infectious diseases (viral or bacterial diseases and diseases causing high fever) (e.g., Nunn 2001, King et al 2002, malnutrition, or general metabolic disorders (deficiencies in diet componentsproteins; vitamins: A, C, D, K; elements: Ca, P, Mg, F) (e.g., Goodman et al 1992, Pitsios andΖafiri 2012). In this respect, the changes classified as general (systemic) are most relevant in population studies (Hillson and Bond 1997, Hillson 2002, King et al 2005, Ritzman et al 2008).…”
Section: Discussionmentioning
confidence: 99%